Relationship of Retinal Vessel Caliber with Age-Related Macular Degeneration - Sara Toulouie; Sean Chang; Julia Pan; Kiersten Snyder; Glenn Yiu (Journal of Ophthalmology)
Purpose. Evaluate the relationship between retinal vascular caliber and age-related macular degeneration (AMD) severity or progression. Methods. A retrospective secondary analysis of 1172 fundus photographs and clinical data from the prospective Age-Related Eye Disease Study (AREDS). Central retinal artery equivalent (CRAE), central retinal vein equivalent (CRVE), and arteriole-to-venule ratio (AVR) were measured using the Parr–Hubbard–Knudtson formula. Univariate and multivariate regressions were used to determine the association of CRAE, CRVE, and AVR with age, sex, smoking status, presence of cilioretinal artery, and AMD severity at baseline and 5 years using the 9-step AMD severity score. Results. Only CRAE and CRVE were higher in men (P<0.001), current smokers (P<0.001), and the eyes with a cilioretinal artery (P=0.009−0.043). AMD severity was greater in older patients (P=0.001), current smokers (P=0.012), the eyes without a cilioretinal artery (P=0.001), and lower AVR (P=0.034) on multivariate regression but was not influenced by CRAE or CRVE (P=0.240−0.500). Choroidal neovascularization (CNV) presence was associated with older age (P=0.003) and absence of a cilioretinal artery (P=0.009), while central geographic atrophy (CGA) was associated with narrower CRAE (P=0.002) and possibly AVR (P=0.046). None of the retinal vessel parameters were predictive of AMD severity score or new onset of CNV or CGA at 5 years. Conclusion. A lower arteriole-to-venule ratio may be associated with AMD severity, with narrower arterioles seen in the eyes with geographic atrophy, suggesting a role of the retinal vasculature in AMD pathophysiology. This trial is registered with ClinicalTrials.gov Identifier: NCT00000145.